First Report on Molecular Characterization of Taenia multiceps Isolates From Sheep and Goats in Faisalabad, Pakistan - Alvi, Mughees Aizaz; Ohiolei, John Asekhaen; Saqib, Muhammad; Tayyab, Muhammad Haleem; Zafar Khan, Muhammad Umar; Li, Li; Aqib, Amjad Islam; Hassan, Ali; Alvi, Anum Aizaz; Qamar, Warda; Fu, Bao-Quan; Yan, Hong-Bin; et al. (Frontiers in Veterinary Science, 2020)
Abstract Coenurus cerebralis is the larval stage of Taenia multiceps commonly found in the brain (cerebral form), intramuscular and subcutaneous tissues (non-cerebral form) of ungulates. Globally, few reports exist on the molecular characterization and genetic diversity of C. cerebralis with none available for Pakistan. The current study molecularly characterized 12 C. cerebralis isolates surgically recovered from sheep(n = 4) and goats (n = 8) from a total of 3,040 small ruminants using a portion of the cytochrome c oxidase subunit 1 (cox1) mitochondrial (mt) gene. NCBI BLAST search confirmed the identity of each isolate.A high haplotype and a low nucleotide diversity with 3 haplotypes from the 12 isolates were observed.The findings suggest the existence of unique haplotypes of C. cerebralis in Pakistan.The negative value of Tajima’s D and the positive value of Fu’s Fs were inconsistent with population expansion,however,the sample size was small.Bayesian phylogeny revealed that all Pakistani isolates alongside the Chinese sequences (obtained from GenBank)constituted a cluster while sequences from other regions constituted another cluster.This is the first molecular study to determine the genetic diversity of C. cerebralis in Pakistan and serves as a foundation for prospective studies on the prevalence and population structure of C. cerebralis in the country.Furthermore, in this study, we amplified only a partial segment of the cox1 gene from a limited sample size.This could have implications on the interpretation of the actual population structure in reality.Thus, we recommend future studies to consider a larger sample size in a massive epidemiological survey for further insights.